2014
DOI: 10.3732/ajb.1300423
|View full text |Cite
|
Sign up to set email alerts
|

Repeated evolution of tricellular (and bicellular) pollen

Abstract: The tricellular condition is not irreversible. Pollen cell numbers are maintained at intermediate frequencies because lower net diversification rates of tricellular lineages are counterbalanced by slower state shifts to the bicellular condition. That tricellular lineages diversify slowly and give rise to bicellular lineages slowly reflects a linkage between the evolution of sporophyte lifestyles and the developmental lability of male gametophytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 80 publications
0
37
0
Order By: Relevance
“…Trinuclear pollen is often observed in herbaceous annuals and weeds. Tricellular pollen is difficult to store, has short viability, high respiratory rate and difficult to germinate in vitro (Shivanna 2003;Williams, Taylor, & O'Meara, 2014). Annona cherimola produces both types of pollen, bicellular and tricellular pollen, in the same plant but high temperatures above 25°C increased the number of tricellular pollen from 5% at 15°C to 60% at 25°C (Lora, Herrero, & Hormaza, 2009).…”
Section: Pollen Viability Morphology and Nucleus Numbermentioning
confidence: 99%
“…Trinuclear pollen is often observed in herbaceous annuals and weeds. Tricellular pollen is difficult to store, has short viability, high respiratory rate and difficult to germinate in vitro (Shivanna 2003;Williams, Taylor, & O'Meara, 2014). Annona cherimola produces both types of pollen, bicellular and tricellular pollen, in the same plant but high temperatures above 25°C increased the number of tricellular pollen from 5% at 15°C to 60% at 25°C (Lora, Herrero, & Hormaza, 2009).…”
Section: Pollen Viability Morphology and Nucleus Numbermentioning
confidence: 99%
“…Analyses of cleared anthers indicated that 9.7% of mature pollen grains contained two sperm cells (n=500), indicating the final generative cell mitosis giving rise to the sperm cells primarily occurs following pollen tube germination. This is also observed in soybean and 70% of flowering plant species (Brewbaker, 1967, Williams et al, 2014, Haerizadeh et al, 2009, Wojciechowski et al, 2004). Anthers and pistils harvested at anthesis were processed to create a transcriptome referred to as mature pollen-sperm cell (MP-SC; see Methods for details).…”
Section: Resultsmentioning
confidence: 55%
“…We also adapted a DAPI stain to visualize pollen preand post-germination, and to establish whether Cannabis sativa was a bicellular or tricellular species, which to our knowledge has not been reported in the literature. Approximately 30% of angiosperms are known to be tricellular, with the male gametophyte sexually immature at the time of anthesis (Williams et al, 2014). We also used the PGA to test how storage and timing of pollen collection could influence germination rates.…”
Section: Introductionmentioning
confidence: 99%